SAT0381 Correlation between three different methods to assess dermal thickness in systemic sclerosis patients with different patterns of nailfold microangiopathy. (15th June 2017) - Ruaro, B; Sulli, A; Alessandri, E; Paolino, S; Ghio, M; Trombetta, AC; Pizzorni, C; Tomatis, V; Cutolo, M
Abstract : Background: Systemic sclerosis (SSc) is characterized by the increase of dermal thickness (DT) (1). The modified Rodnan skin score (mRss) is the validated method to evaluate the severity of skin impairment (2, 3). Several studies have reported the capability of high frequency skin ultrasound (US) to reflect the overall severity of the skin damage in SSc patients (4–5). The plicometer skin test (PST) is another method to evaluated cutaneous involvement in SSc patients (6). Objectives: The aim of this study was to identify possible correlations between US, mRss and PST to evaluate DT in SSc patients with different patterns of nailfold microangiopathy. Methods: Sixty-three SSc patients (mean age 64±11SD years, mean disease duration 7±6 years, 43 lcSSc and 20 dcSSc) and 63 sex and age matched healthy subjects were enrolled after written informed consent. All subjects were assessed by mRss, US and PST to evaluate the DT in the seventeen skin areas of the body usually evaluated by mRss (zygoma, fingers, hands, dorsum of hands, forearms, arms, chest, abdomen, thighs, legs, feet) (1–6). Nailfold videocapillaroscopy (NVC) was used to assess the proper pattern of microangiopathy and to calculate the microangiopathy evolution score (MES) (7–8). Statistical evaluation was performed by non-parametric tests. Results: As expected, the group of SSc patients had a statistically significant higher DT, as evaluated by the three methods, at level of all areas when compared to the control group (p=0.0001). All methods demonstrated a progressively higher DT in patients with "Early", vs. "Active" and vs "Late" pattern of nailfold microangiopathy (p<0.005), and a positive correlation was observed with MES (r=0.71 p<0.001). A positive correlation was observed in SSc patients between the three method to evaluate DT (PST vs mRss r=0.98, p<0.0001; PST vs US r=0.53, p<0.0001; US vs mRss r=0.53, p<0.0001). Conclusions: This study demonstrates a relationship between different methods to assess DT (US, mRss and PST) in SSc patients and a relationship between skin damage and microangiopathy impairment. References: Moore TL, et al. Rheumatology 2003;42:1559–63. Sulli A, et al. Ann Rheum Dis. 2014;69:1140–3. Kaldas M, et al. Rheumatology 2009;48:1143–6. Hesselstrand R, et al. Rheumatology 2008;47:84–7. Kaloudi O, et al. Ann Rheum Dis. 2010;69:1140–3. Parodi MN, et al. Br JRheumatol. 1997;36:244–50. Sulli A, et al. Ann Rheum Dis 2008;67:885–7. Cutolo et al. J Rheumatol 2000; 27;155.60. Disclosure of Interest: None declared